COMPARISON OF INTRAPERITON EALBUPIVACAIE WITH INTRAVENOUS TRAMADOL HYDROCHLORIDE FOR POSTOPERATIVE PAIN RELIEF AFTER LAPAROSCOPIC CHOLECYSTECTOMY - Gohar latif Kalas; Fahad Hafeez Khan; Kamran Hakeem Khan; Nadeem Malik; Ishtiaq Anwar (Journal of University Medical & Dental College, 2019)
OBJECTIVE: To determine the eﬃcacy of intraperitoneal bupivacaine in post operative pain relief following cholecystectomy in comparison with intravenous tramadol.STUDY DESIGN: Randomized Controlled Trial (RCT)PLACE & DURATION OF STUDY: Study was conducted at surgery department in PIMS, Islamabad for duration of 8 months (June 2015 to January 2016).PATIENTS AND METHODS: A sample size of 272 patients was calculated. Non probability consecutive sampling is used for patient selection. Patients were divided into two equal groups. Group A (IV tramadol group) was a control group while Group B (intraperitoneal bupivacaine group) was studied group. Study outcome was measured in terms of pain relief one hour after surgery, time of ﬁrst rescue analgesic injection, number of rescue analgesic injections and time of mobilization.RESULTS: Demographic characteristics were not signiﬁcantly diﬀerent between both groups. Mean VAS for pain relief at 1 hour following surgery was found to be 4.4 ±1.7 SD in control group A while 3.5 ±1.71 SD (P<0.05) in study group. Statistically signiﬁcant (P<0.05) diﬀerence was found among both groups in mean time of ﬁrst rescue injection (2.3 hours ±0.86SD VS 3.6 hours±1.33SD), mean number of rescue injections (1.5 ±0.7SD VS 0.9 ±0.57 SD) and mean mobilization time (3.5 hours ±1.3SD VS 2.2 hours ±0.85SD).CONCLUSIONS: Intraperitoneal bupivacaine is an eﬀective treatment option for controlling postoperative pain and other associated morbidities following LC.